Therapeutic Potential of Targeting Ferroptosis in Periprosthetic Osteolysis Induced by Ultra-High-Molecular-Weight Polyethylene Wear Debris - Takuya Ogawa; Shunichi Yokota; Liyile Chen; Yuki Ogawa; Yoshio Nishida; Taiki Tokuhiro; Hend Alhasan; Tomoyo Yutani; Tomohiro Shimizu; Daisuke Takahashi; Takuji Miyazaki; Tsutomu Endo; et al. (Biomedicines)
Background/Objectives: Periprosthetic osteolysis is the primary cause of arthroplasty failure in the majority of patients. Mechanistically, wear debris released from the articulating surfaces of a prosthesis initiates local inflammation and several modes of regulated cell death programs, such as ferroptosis, which represents a promising therapeutic target in various chronic inflammatory diseases. Thus, the current study aimed at exploring the therapeutic potential of targeting ferroptosis in a polyethylene-wear-debris-induced osteolysis model. Methods: Inverted cell culture model was used for stimulating the cells with wear debris in vitro, and calvarial osteolysis model was used for evaluating the therapeutic effects of inhibitors in vivo. Results: The immunostaining of periprosthetic bone tissues demonstrated a number of osteocytes expressing ferroptosis markers. Likewise, the expressions of ferroptosis markers were confirmed in polyethylene-wear-debris-stimulated osteocyte-like cells and primary osteoblasts in a direct stimulation model but not in an indirect stimulation model. Furthermore, polyethylene wear debris was implanted onto calvarial bone and mice were treated with the ferroptosis inhibitors DFO and Fer-1. These treatments alleviated the inflammatory and pathological bone resorption induced by the wear debris implantation. Conclusions: Our data broaden the knowledge of the pathogenesis of periprosthetic osteolysis and highlight ferroptosis as a promising therapeutic target.